Do we control gastric residuals unnecessarily in premature newborns? AGRA study: avoidance of gastric residual aspiration - Selahattin Akar; Mehmet Turgut (BMJ Publishing Group, 2020)
Methods Preterm infants with a gestational week ≤33 were included in the study. The group with gastric residual control before each feeding consisted of 169 infants, and the group without routine gastric residual aspiration included 122 infants.Results The mean gestational week was 30.37±2.58 and 29.31±3.37 in the group with gastric residual control and in the group without routine residual control, respectively (p<0.05). Birth weight, male gender, and mode of delivery were similar between both groups. The time to full enteral intake was shorter in the group without routine residual control (p<0.05). Total durations of parenteral nutrition, ≥grade 2 NEC, weight at discharge and duration of hospitalization were similar between the groups. Duration of invasive mechanical ventilator support was shorter in the group without routine residual control.Conclusion Avoidance of routine gastric residual aspiration in preterm infants shortens the time to full enteral intake without increasing the incidence of NEC.